Effects of Herbal Adaptogen Feed-Additive on Growth Performance, Carcass Parameters, and Muscle Amino Acid Profile in Heat-Stressed Modern Broilers - Greene, Elizabeth S.; Maynard, Clay; Owens, Casey M.; Meullenet, Jean-François; Dridi, Sami (Frontiers in Physiology, 2021)
Heat stress has strong adverse effects on poultry production and, thereby, threats its sustainability, which energized scientists to search for innovative and effective solutions. Here, we undertook this study to evaluate the effects of in-feed herbal adaptogen (stress response modifier) supplementation on growth performances, meat quality, and breast amino acid profile in chronic cyclic heat-stressed broilers. Day-old male Cobb 500 chicks (n=720) were randomly assigned, in environmental chambers (n=12, 24 pens), to 3 diet-treatments: a 3-phase corn-soybean based diet fed as such (Control, C), or supplemented with the herbal adaptogen at 500g/1000kg control diet (NR-PHY-500) or at 1kg/1000 kg control diet (NR-PHY-1000). From d29 to d42, birds from 9 chambers were exposed to cyclic heat stress (HS, 35°C from 9:30 am-5:30 pm), however the rest of the chamber were maintained at thermoneutral conditions (24°C, TN), which creates 4 experimental groups: C-TN, C-HS, NR-PHY-500HS, and NR-PHY-1000HS (6 pens/group, 168 birds/group). HS altered growth performance via depression of feed intake and body weight. Adaptogen supplementation stimulated feed intake and averaged 65.95g and 83.25g better body weight and 5 and 10 points better FCR at low and high dose, respectively, compared to heat-stressed birds. This increase in body weight was mirrored in enhanced weights of body parts (breast, tender, wings, and legs). Adaptogen supplementation modulated also breast amino acid profile, pH, color, and quality. Together, these data suggested that adaptogen supplementation could be a promising solution to alleviate heat stress, however further in-depth investigation for its mode of action and its underlying mechanisms are warranted.